LIMITS TO PARTICIPATION: A CRITICAL (DE)CONSTRUCTION OF STRATEGIC PLANNING IN A PUBLIC INSTITUTION OF HIGHER EDUCATION - Castro, Eglalciane de Lyrio Tongo; Foletto, Rosieli Geraldina Merotto; Tonon, Camila Bruschi (Seven Editora, 2026)
The aim of this work is to understand, critically, as is characterized the construction of strategic planning within a campus on IFES, from the communicative action of the administrative technicians staff (TAE) classes C, D and E and immediate supervisors. Thus, Jürgen Habermas's Communicative Action Theory (CAT) and its proposal for deliberative democracy were undertaken as a theoretical framework for understanding this process. This work is characterized as qualitative research. Empirical data were produced by desk research, participant observation and semi-structured interviews. The content analysis was used for the treatment of interviews. The results indicate that the construction of strategic planning is characterized as a strategic space to reach the success and not the understanding, where attention to collective interests is subordinate to the quest for greeting of legislation and the achievement of results.DOI: https://doi.org/10.56238/sevened2026.001-020